Hospesneotomae n. gen. of the Triatomini tribe presents a turnaround in the taxonomy of the Triatoma protracta species complex - de Paiva, Vinícius Fernandes [UNESP]; de Oliveira, Jader [UNESP]; Belintani, Tiago [UNESP]; Galvão, Cleber; Gil-Santana, Hélcio Reinaldo; da Rosa, João Aristeu [UNESP] (Springer Nature, 2025)
The Triatominae are of relevant public health importance because they include hematophagous species which are proven or potential vectors of Chagas disease. Currently, eighteen genera are considered valid in this subfamily. Through a comprehensive and integrative study, the description of a new genus of Triatomine, the nineteenth of the subfamily, is presented. Were generated a robust phylogeny from data deposited in Genbank, created a table comparing two genera with Hospesneotomae, and prepared a dichotomous key for the genus and species. To this end, several systematic pieces of evidence about this group were taken into consideration, such as morphology, genetics, ecotopes and species distribution. The new genus is proposed to include the species previously included in the T. protracta complex, considered now in a new taxonomic assignment. Therefore, Hospesneotomae n. gen. will be composed by the following seven species (in the new combination): H. protracta, H. barberi, H. incrassata, H. peninsularis, H. sinaloensis, H. neotomae and H. nitida, providing an innovative perspective in understanding these organisms, because the seven species grouped here in the proposed new genus are distinct from the others species of Triatoma and at the same time show similarities that indicates that they form a monophyletic group.